From the Soviet Folksong Research: Between Free Choice and Obligation - Stundžienė, Bronė (Tautosakos darbai, 2023)
The history of the Soviet folkloristics has been underresearched until now. Usually, attention in centered only on the main directions and results of the works carried out during that period. In these folksong studies, these include creating classification system for folksong genres, as well as editing and publishing so-called fundamental sources of folklore – the multivolume collection of the “Book of Lithuanian Folk Songs”. So far, the generation of the Soviet-period folklorists or research activities of its representatives, especially the options and alternatives that were available to them, have hardly been discussed, if at all. The 100th anniversary of Pranė Jokimaitienė, which was celebrated last year, encouraged to take a look at her folklore studies precisely in the context of the Soviet ideological demands, which were relevant to this sphere of research. However, her case is rather exceptional, since the biography of this scholar, who grew up during the interwar period in the independent Lithuania, was for various reasons completely inappropriate to the Soviet regime. Therefore, a fresh look at the folklore studies by P. Jokimaitienė written during the Soviet-period, and observations in the field of possible ideological tensions that can be discerned in them enables to identify a very strong person who, while moderately using the “inner censor” tool that was common in the public discourse, at the same time managed to resist any moral compromises. The interpretation of research works by P. Jokimaitienė proposed in the article allows us to draw a conclusion that, while following the unified Soviet program for folklore research, she never did anything superficially – both investigating the folksong composition as a social or artistic discourse and writing popular texts on folklore. Most of her arguments are well documented and constructive, while her notion of folksongs is based on philological assumptions and still relevant to the Lithuanian folkloristics today.